Species limits in antbirds (Aves: Passeriformes: Thamnophilidae): an evaluation of Frederickena unduligera (Undulated Antshrike) based on vocalizations - Isler, Morton L.; Isler, Phyllis R.; Whitney, Bret M.; Zimmer, Kevin J.; Whittaker, Andrew (Zootaxa, 2009)
The Undulated Antshrike, Frederickena unduligera, a resident of lowland humid forests of western Amazonia, is somewhat poorly known as a result of its low population density and retiring habits. In recent years, vocalizations of F. unduligera have been recorded sufficiently to permit geographic analysis. Vocalizations supply valuable measures of species limits for antbirds, whose vocalizations are thought not to be learned. Based on vocalizations, we found that populations of the Undulated Antshrike are more appropriately considered as two biological species. Three populations considered subspecies of F. unduligera await further evaluation pending the acquisition of additional vocal recordings, specimens, and tissue for genetic analysis.